Lactobacillus fermentum ZS40 Ameliorates Inflammation in Mice With Ulcerative Colitis Induced by Dextran Sulfate Sodium - Chen, Zixia; Yi, Long; Pan, Yanni; Long, Xingyao; Mu, Jianfei; Yi, Ruokun; Zhao, Xin (Frontiers in Pharmacology, 2021)
Ulcerative colitis is an inflammatory disease of the intestine caused by many reasons, and it may even develop into colon cancer. Probiotics are normal bacteria that exist in the human body and have been proven to regulate the balance of intestinal flora and alleviate inflammation. The current study aimed to study the effect of Lactobacillus fermentum ZS40 (ZS40) on dextran sulfate sodium (DSS)-induced ulcerative colitis mice. The length and weight of the colon were measured, and the histopathological morphological changes of colon tissue were observed to evaluate the effects of ZS40 on colitis. Biochemical kits, ELISA kits, real-time quantitative PCR (RT-qPCR), and western blot were also used to detect the effects of ZS40 on serum and colon tissue related oxidative indicators and pro-inflammatory and anti-inflammatory cytokines. We found that ZS40 could reduce colonic inflammatory cell infiltration and goblet cell necrosis, increase total superoxide dismutase and catalase in mouse serum, and reduce myeloperoxidase and malondialdehyde levels. ZS40 could down-regulate the level of proinflammatory cytokines and up-regulate the level of anti-inflammatory cytokines. More importantly, ZS40 down-regulated the relative expression of nuclear factor-κB p65 (NF-κBp65), IL-6, and TNF-α mRNA and protein, up-regulated the relative expression of inhibitor kapa B alpha (IκB-α). By regulating the NF-κB and MAPK pathways to down-regulated the relative expression of p38 and JNK1/2 mRNA and p38, p-p38, JNK1/2, and p-JNK1/2 proteins. Our study suggested that ZS40 may serve as a potential therapeutical strategy for ulcerative colitis.